2003
DOI: 10.1073/pnas.0536089100
|View full text |Cite
|
Sign up to set email alerts
|

Separable features of visual cortical plasticity revealed by N -methyl- d -aspartate receptor 2A signaling

Abstract: How individual receptive field properties are formed in the maturing sensory neocortex remains largely unknown. The shortening of N-methyl-D-aspartate (NMDA) receptor currents by 2A subunit (NR2A) insertion has been proposed to delimit the critical period for experience-dependent refinement of circuits in visual cortex. In mice engineered to maintain prolonged NMDA responses by targeted deletion of NR2A, the sensitivity to monocular deprivation was surprisingly weakened but restricted to the typical critical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 61 publications
(122 reference statements)
11
146
0
Order By: Relevance
“…Indeed, enrichment in the adult causes changes in the NMDA receptor expression and in the expression of downstream molecules (Rampon et al, 2000;Molteni et al, 2002). NMDA receptors have been demonstrated to play a crucial role in ocular dominance plasticity and in development of receptive field properties in the visual cortex (Bear et al, 1990;Roberts et al, 1998;Ramoa et al, 2001;Fagiolini et al, 2003) and to be highly sensitive to activity (Quinlan et al, 1999;Philpot et al, 2001). Interestingly, Liu et al (2000) have shown that maternal care affects NMDAR subunit expression in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, enrichment in the adult causes changes in the NMDA receptor expression and in the expression of downstream molecules (Rampon et al, 2000;Molteni et al, 2002). NMDA receptors have been demonstrated to play a crucial role in ocular dominance plasticity and in development of receptive field properties in the visual cortex (Bear et al, 1990;Roberts et al, 1998;Ramoa et al, 2001;Fagiolini et al, 2003) and to be highly sensitive to activity (Quinlan et al, 1999;Philpot et al, 2001). Interestingly, Liu et al (2000) have shown that maternal care affects NMDAR subunit expression in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Second, NR2A upregulation and NR2B downregulation do not match the end of critical periods 45 . Third, NR2A knockout mice have critical periods of normal duration in somatosensory and visual cortices 44,46 . Notably, the onset of PACSIN1 expression and concomitant downregulation of synaptic NR3A (Fig.…”
Section: Endocytosis and Synapse Developmentmentioning
confidence: 99%
“…Receptors for glutamate, especially NMDA receptors, are intimately involved in the early formation of the central nervous system (CNS), being required for neuronal migration (Komuro and Rakic, 1993;Behar et al, 1999), axonal and neurite growth in the foetus and postnatally, neurite extension and branching (Heng et al 1999;Cuppini et al 1999;Rajan and Cline 1998), spine formation and stability (Alvarez et al, 2007;Ultanir et al, 2007), the formation and stability of synapses (Colonnese et al, 2005) and neuronal plasticity (Fagiolini et al,. 2003;Iwasato et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NMDAR contribute to the programmed cell death which shapes the early nervous system by eliminating a proportion of neurons. Many of these same factors are involved in neuronal plasticity in the postnatal brain (Fagiolini et al, 2003;Iwasato et al, 2000). Indeed, it has been proposed that tissue formation and polarity may be determined largely by a gradient for a signal antagonist, such as kynurenic acid, rather than an agonist (Gurdon and Bourillot, 2001).…”
mentioning
confidence: 99%